Beach Erosion in the Gulf of Castellammare di Stabia in Response to the Trapping of Longshore Drifting Sediments of the Gulf of Napoli (Southern Italy) - Micla Pennetta (Geosciences, 2018)
The results of this study have allowed verification that longshore sediment transport along the coast of Napoli Gulf (southern Italy) takes place from Northwest to Southeast. The current analysis describes the results of an integrated sedimentological and geomorphological study of the Neapolitan coastal area. A sedimentological and morphosedimentary study was carried out by bathymetric survey and sampling of bottom sediments. The analysis of modal isodensity curves shows that all the sediments are moved from NW to SE by longshore currents parallel to the coastline. The morphological evolution of the Castellammare di Stabia Gulf coastal area, based on historical coastline changes, starts from 1865, when the sandy littoral was wide and in its natural state. Since the construction of the Torre Annunziata harbor in 1871, sediments transported by a NW-SE longshore drift have become trapped, inducing the genesis of a new wide triangular-shaped beach on the updrift side (NW) of the harbor breakwall. This process induced a significant shoreline retreat of the south-east sector of the littoral. Widespread beach erosion of the coastal physiographic unit of Castellammare di Stabia Gulf (delimited by two ports) is more developed in the southern portion. This study highlights a slight rotation of the shoreline toward the East and a general trend of regression, with typical overall accentuation of shoreline concavity, and significant widening of the triangular-shaped beaches at the end of the falcate. This reduced sediment input removed from the sedimentary budget a large amount of deposits, which are hardly restorable due to the scarce supply of sediment load by the Sarno river and its tributaries. In addition to this new and important derived morphologic feature, other recent human interventions have contributed to further modifications of morphologic characteristics of emerged and submerged beach. The intense use of the territory caused modifications on both the fluvial course and river mouth with direct and indirect effects on the shoreline and the drainage network of the Sarno River.